A Low-Maintenance Approach to Improving Retention: Short On-Line Tutorials in Elementary Statistics. (February 2013) - Sargent, Carol Springer; Borthick, A. Faye; Lederberg, Amy R.; Haardörfer, Regine
The struggle to get weak students to use learning support services plagues virtually all retention programs (Friedlander, 1980; Hodges, 2001; Karabenick & Knapp, 1988; Moore & LeDee, 2006; Simpson, Hynd, Nist, & Burrell, 1997; Webster & Dee, 1998). This study presents a cost-effective form of supplemental instruction (SI), in the form of on-line tutorials, ultra-short digital instruction suitable for high enrollment courses, designed to engage underprepared or poorly motivated students pass their required courses. Participation among the low achievers was 39.3%, improving their exam scores about a half a letter grade over non-users and students in control sections, even without giving course credit for using the SI resource. Surveys reveal what aspects of the tutorials were most effective and valued.